Internal Quality Assurance System to Improve Lecturer Performance and Its Relevance to Education Quality at ITB Swadharma - Warta, Waska; S, Usanto; Sopian, Adi (Journal of Applied Science, Engineering, Technology, and Education, 2023)
To improve teacher performance and education quality at ITB Swadharma, this research explains the Internal Quality Assurance System (IQAS). The qualitative case study research focuses on ITB Swadharma's Quality Assurance Institute (QAI). Data collection methods include direct observation, document and archival searches, and interviews. The research shows that IQAS at ITB Swadharma improves education through research and innovation. ITB Swadharma can improve inclusivity, relevance, and comprehensiveness by focusing on program evaluation, student empowerment, technology implementation, industry collaboration, internal quality monitoring, stakeholder engagement, and best practices adoption. The institution can better adapt to education sector and student needs with IQAS. ITB Swadharma can improve educational quality by incorporating students, alumni, staff, the local community, and industry partners. According to ITB Swadharma's QAI's academic and quality documents, the IQAS Cycle implements IQAS policies and ideas. Leadership commitment, auditor shortages, and IQAS routineness are issues. Quality assurance expertise, auditor training, and a culture of quality assurance address these issues. The results of annual IQAS examination are used to promote quality. Quality management criteria from the National Accreditation Board for Higher Education (BAN PT) and the Independent Accreditation Agency (LAM) influence IQAS implementation.